Московская битва 1612 года - Коваленко Денис Леонидович (Серия "Великие битвы России", 2021)
Экземпляры: ф.1 (20220606) / Инвентарный номер: 62288 / Цена: / Сис.шифр: 63.3(2)44 / Авт.знак: К 56 / ГРНТИ: 03.23.31 / ББК: 63.3(2)44